Kekerassan Verbal dengan Motivasi Menolong Korban pada Relawan PMI di Surabaya - Widyastuti, Merina; Oktaningtiyas, Oktaningtiyas; Rustini, Sri Anik; Sari, Ninik Ambar; Hayati, Ceria Nur; Rofi’ah, Ika Ainur (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2023)
A volunteer is someone who contributes their time, energy, and skill to meet the needs of a community without any financial benefit from the contribution. Verbal abuse is an utterance towards someone that is considered demeaning, insulting, racist, or degrading using a high-pitched voice, because this form of psychological violence can attack a person's emotional or mental state. Motivation is a person's encouragement in acting to carry out activities to achieve certain goals. The aim of the study is to analyze the relationship between verbal abuse and the motivation to help victims among PMI volunteers in Surabaya. The research design used is a correlational descriptive analysis that analyzes the relationship between verbal abuse and the motivation to help victims of PMI volunteers in Surabaya. The approach in this research is cross-sectional. The sampling technique in this study uses probability sampling. The population in this study are 121 members of KSR PMI Surabaya, with a total sample that met the inclusion and exclusion criteria of 93 people. Data collection uses a questionnaire about verbal abuse that consists of 30 questions, reliability and validity test with a result of 0.0703, and a motivational questionnaire consisting of 30 questions using the Volunteer Function Inventory (VFI) questionnaire. The data is then tested using the Spearman Rho Correlation test. The results showed that the majority of respondents experienced high verbal abuse when helping victims as much as 77.4%. Most of the respondents had a strong motivation when helping victims as much as 36.6%. The results showed that there was a relationship between verbal abuse and motivation to help victims in PMI volunteers in Surabaya with a correlation test showing an r value of 0.513 with a value of <0.001. The high level of verbal abuse on PMI volunteers requires strong motivation. This requires support from family and fellow volunteers who always provide encouragement and strength when helping victims.